Low temperature ferroelectricity in Strontium Titanate domain walls detected by depolarization pyrocurrents. (September 2021) - Cabassi, R.; Checchia, S.; Trevisi, G.; Scavini, M.
Abstract: The low temperature phenomenology of Strontium Titanate is rich and intriguing, with anomalies producing signals of small intensity. We show that depolarization pyrocurrents are a suitable technique to greatly enhance these features, otherwise rather elusive when observed with other methods. Depolarization currents have been measured on a single phase sintered SrTiO3 pellet, prepared by solid state reaction. They increase with increasing poling voltage and switch to symmetric negative values by inversion of the poling sign, which is a property commonly considered as a clue of ferroelectricity. Moreover, three intensity maxima are revealed at T=16, 24 and 45 K respectively. In particular, the anomaly at T ≃ 45 K can be associated with the emerging of ferroelectricity in walls between antiphase ferroelastic domain walls, whose nanoscale polar character is already known from literature.We demonstrate and estimate such ferroelectricity reconstructing a static polarization hysteresis loop by applying suitable poling patterns. Highlights: Strontium Titanate at low temperatures exhibits intriguing but elusive anomalies. The phenomenology can be enhanced by measuring pyroelectric depolarization currents. Structural domain walls (DW) are expected to have ferroelectricity of tiny magnitude. We observe pyroelectric peaks related to DW ferroelectricity. DW polarization loop is obtained by proper pyroelectric polarization patterns.